A novel synchronized motion method for direct and point-to-point robot trajectory planning in constrained workspace - Kandil, Amr A.; Badreddin, Essameddin (IEEE International Conference on Systems, Man and Cybernetics, 2008, 2008)
This paper proposes a novel method for planning point-to-point robot trajectories. With the new method, the requirement of an optimal path and the need of a slim motion due to the lack of free space can be compromised. The generated slim motion is suitable for applications where human-robot cooperation takes place. The new method is based on the synchronized links motion with a constant ratio of the link angle positions. The new method of synchronized motion was illustrated using a two-degree-of freedom (DOF) planar robot and compared with conventional methods.
Gesehen am 13.06.2019